“MAX” Robot Pintar Berpendingin Mesin Dengan Sensor Suhu LM35 Berbasis Arduino UNO328P - Wahyuadnyana, Kadek Dwi; Wibawa, I Made Satriya (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana), 2019)
It has been successfully created a robot named "MAX". MAX Robot uses 2 (two) main sensors, those are ultrasonic sensors as sensors that detect an objects and LM35 temperature sensors as sensors to detect and monitor the temperature of the robotic machines. Both sensors are connected and controlled by ATMega328P microcontroller based Arduino Uno. The results of the readings from the temperature sensor on the robot's body will be displayed to the Light Crystal Display (LCD). The MAX robot is able to detect objects effectively at a distance of ±25 cm, then the robot stops and then turns in a certain direction by considering the distance of the object around the robot body. If a barrier is not detected, the MAX robot runs straight. In addition, the MAX robot is also able to detect and monitor engine temperature on its own and is able to automatically activate engine coolers when the engine temperature is above the set – point (hot) and non-active again when the engine is in normal temperature.